1988
DOI: 10.1128/cmr.1.3.268
|View full text |Cite
|
Sign up to set email alerts
|

Detection of urinary tract infections by rapid methods

Abstract: A review of rapid urine screens for detection of bacteriuria and pyuria demonstrates a number of available alternatives to the culture method. Selection of one or more of these systems for routine use is dependent upon the laboratory and the patient population being tested. The laboratory approach to the diagnosis of urinary tract infection should consider the clinical diagnosis of the patient whenever possible. Keeping in mind that quantitative urine cultures alone cannot be used to detect infection in some p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
79
2
2

Year Published

2004
2004
2022
2022

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 121 publications
(86 citation statements)
references
References 98 publications
3
79
2
2
Order By: Relevance
“…Two multiplicities of infection were selected for all further experiments: 0.1 and 1, respectively and the infection period selected was 2 h. Furthermore, two different E. coli concentrations which resulted in approximately 105 CFUml -1 of adhered cells after 60 min were also selected for the adhesion and phage infection studies, 106 and 107 CFUml -1 , respectively (data not shown). It is important to have this concentration of adhered cells since typically a urinary tract infection is characterized by a positive uroculture of more than 105 CFUml -1 [11,12]. The reduction percentages of bacterial cells adhered to urothelium (A columns in Figs.…”
Section: Phage Infection Of Bacteria Suspended or Adhered To Urotheliummentioning
confidence: 99%
“…Two multiplicities of infection were selected for all further experiments: 0.1 and 1, respectively and the infection period selected was 2 h. Furthermore, two different E. coli concentrations which resulted in approximately 105 CFUml -1 of adhered cells after 60 min were also selected for the adhesion and phage infection studies, 106 and 107 CFUml -1 , respectively (data not shown). It is important to have this concentration of adhered cells since typically a urinary tract infection is characterized by a positive uroculture of more than 105 CFUml -1 [11,12]. The reduction percentages of bacterial cells adhered to urothelium (A columns in Figs.…”
Section: Phage Infection Of Bacteria Suspended or Adhered To Urotheliummentioning
confidence: 99%
“…All individuals may be susceptible to UTIs; however, the prevalence of infection differs with age, sex and certain predisposing factors (Griebling 2001). The incidence of infection is greater in females than in males with two exceptions, infants and the catheter related infections (Kunin 1987, Pezzlo 1988. Women tend to get UTIs more often because their urethra is shorter and closer to the anus than men and hence the pathogenic bacteria get quick access to the bladder.…”
Section: Introductionmentioning
confidence: 99%
“…Current bacteria detection methods include urine cultures [9] and biosensor techniques that detect antigen-antibody, enzyme-substrate, or receptor-ligand complexes by measuring fluorescent light, surface reflection, and electrical properties [10][11][12][13]. These methods can be time and labor consuming (12-24 hours for urine culture), expensive, or complex to operate.…”
Section: Resultsmentioning
confidence: 99%